2018
DOI: 10.1016/j.celrep.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Organoid Models of Human Liver Cancers Derived from Tumor Needle Biopsies

Abstract: SummaryHepatocellular carcinoma (HCC) is the most common primary liver cancer and the second most frequent cause of cancer-related mortality worldwide. The multikinase inhibitor sorafenib is the only treatment option for advanced HCC. Due to tumor heterogeneity, its efficacy greatly varies between patients and is limited due to adverse effects and drug resistance. Current in vitro models fail to recapitulate key features of HCCs. We report the generation of long-term organoid cultures from tumor needle biopsie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
339
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 345 publications
(351 citation statements)
references
References 48 publications
11
339
1
Order By: Relevance
“…One case of third-and fourth-line chemotherapy also exhibited lack of sensitivity to docetaxel. Our results highlight the applicability of patientderived organoid drug screens to predict clinical outcome [20] and their correlation with genomic and transcriptomic features of the primary tumor, as shown in recent studies for lung [56], gastrointestinal cancer [20], hepatocellular carcinoma [57] and ovarian cancer [58]. The panel of drugs can be adapted depending on the individual patient profile e.g.…”
Section: Ar-blocker Enzalutamide Was Effective Only In the Androgen-dsupporting
confidence: 61%
“…One case of third-and fourth-line chemotherapy also exhibited lack of sensitivity to docetaxel. Our results highlight the applicability of patientderived organoid drug screens to predict clinical outcome [20] and their correlation with genomic and transcriptomic features of the primary tumor, as shown in recent studies for lung [56], gastrointestinal cancer [20], hepatocellular carcinoma [57] and ovarian cancer [58]. The panel of drugs can be adapted depending on the individual patient profile e.g.…”
Section: Ar-blocker Enzalutamide Was Effective Only In the Androgen-dsupporting
confidence: 61%
“…In C284b, the correlation between the human HCC and the PDX tumors was weaker than in other cases. This is likely explained by the loss of the trabecular growth pattern in the PDX tumor and the lower tumor content in the biopsy (<30% according to WES‐based CNA analysis; data not shown). Furthermore, HCC‐specific expression of somatic mutations in cancer genes was maintained in the corresponding PDX models.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, routine liver biopsy remains the gold standard for diagnosis of NASH and if performed optimally poses minimal risk to the patient (23,27,28). Indeed needle biopsies have recently been reported to be sufficient for derivation of liver cancer organoids from patient liver (29) despite the fact that they actually grow more slowly in organoid culture than normal liver organoids (30). We noticed that normal donor liver derived organoids are not only bipotent but can repeatedly convert from the biliary state to the hepatic state and back to the biliary state, closely reflecting the situation in vivo, as several careful lineage tracing studies in mice have shown (16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%